Shower power: isolating the prompt atmospheric neutrino flux using electron neutrinos - Beacom, John F. (2004)
At high energies, the very steep decrease of the conventional atmospheric component of the neutrino spectrum should allow the emergence of even small and isotropic components of the total spectrum, indicative of new physics, provided that they are less steeply decreasing, as generically expected. One candidate is the prompt atmospheric neutrino flux, a probe of cosmic ray composition in the region of the knee as well as small-x QCD, below the reach of collider experiments. A second is the diffuse extragalactic background due to distant and unresolved AGNs and GRBs, a key test of the nature of the highest-energy sources in the universe. Separating these new physics components from the conventional atmospheric neutrino flux, as well as from each other, will be very challenging. We show that the charged-current electron neutrino 'shower' channel should be particularly effective for isolating the prompt atmospheric neutrino flux, and that it is more generally an important complement to the usually considered charged-current muon neutrino 'track' channel. These conclusions remain true even for the low prompt atmospheric neutrino flux predicted in a realistic cosmic ray scenario with heavy and varying composition across the knee (Candia and Roulet, 2003 J. Cosmol. Astropart. Phys. JCAP09(2003)005). We also improve the corresponding calculation of the neutrino flux induced by cosmic ray collisions with the interstellar medium.